Lemma 1:
If:
gcd(e,f)=1
e divides k
f divides k
Then:
ef divides k
Proof:
(1) Assume that ef does not divide k.
(2) Then, there must exist a prime p and a power c such that pc divides ef but pc does not divide k.
(3) Since gcd(e,f)=1, it follows that pc must entirely divide e or pc must entirely divide f.
(4) Let's assume that pc divides e. [We can make a parallel argument if pc divides f.
(5) But then we have a contradiction since e divides k implies that pc divides k.
(6) So we reject our assumption in step #1.
QED
Lemma 2:
If a ≥ b and b ≥ a, then a = b
Proof:
(1) a ≥ b
(2) So it follows that a = b or a is greater than b.
(3) But a is not greater than b since b ≥ a.
(4) So then it follows that a = b.
QED
Corollary 2.1:
If a,b are positive and a divides b and b divides a, then a = b
Proof:
(1) If a divides b, then b ≥ a.
(2) If b divides a, then a ≥ b
(3) Since a ≥ b and b ≥ a, we can use Lemma 2 above to conclude that a= b.
QED
Lemma 3:
if gcd(e,f)=1 and e divides af
then:
e divides a
Proof:
(1) Assume that e does not divide a.
(2) Then, there exists a prime p such that pc divides e but does not divide a.
(3) Since pc divides e, it follows that pc must divide af.
(4) Using Euclid's Lemma (see Lemma 2, here), we know that if p divides af, then it divides a or it divides f. But it cannot divide f since gcd(e,f)=1 so it divides a.
(5) But then pc must divide a since no p can divide f. This contradicts step #2.
(6) Therefore, we reject our assumption in step #1.
QED
Saturday, January 05, 2008
Wednesday, January 02, 2008
Cyclotomic Equation
Lemma 1:
Let ζ = the n-th root of unity where ζ ≠ 1
Then:
1 + ζ + ζ2 + ... + ζn-1 = 0
Proof:
(1) Since ζn = 1, we have:
1 + ζ + ζ2 + ... + ζn-1 = ζ(1 + ζ + ζ2 + ... + ζn-1)
(2) Now ζ ≠ 0 [since 0n ≠ 1] and ζ ≠ 1
(3) Let x = 1 + ζ + ζ2 + ... + ζn-1
(4) Assume that x ≠ 0
(5) So, x = ζx [from step #1]
(6) Since we assume x ≠ 0, we can divide both sides by x to get 1 = ζ
(7) But this contradicts step #2 so we reject our assumption in step #3 and conclude that:
1 + ζ + ζ2 + ... + ζn-1 =0
QED
Corollary 1.1:
if ζ is a primitive n-th root of unity, then:
a = (-a) ζ + (-a)ζ2 + ... + (-a)ζn-1
Proof:
(1) From Lemma 1 above:
-1 = ζ + ζ2 + ... + ζn-1
(2) So, a = (-a)(ζ + ζ2 + ... + ζn-1 ) = (-a) ζ + (-a)ζ2 + ... + (-a)ζn-1
QED
Lemma 2:
if i ≡ j (mod q)
and
ζ is a primitive qth root of unity
Then:
ζi = ζj
Proof:
(1) i ≡ j (mod q) implies there exists integers r,s such that:
i +r*q = j + s*q
(2) So, it follows that:
ζi*(ζq)r = ζj*(ζq)s
(3) Since ζq = 1, we have:
ζi*1r = ζj*1s
which means that:
ζi = ζj
QED
Let ζ = the n-th root of unity where ζ ≠ 1
Then:
1 + ζ + ζ2 + ... + ζn-1 = 0
Proof:
(1) Since ζn = 1, we have:
1 + ζ + ζ2 + ... + ζn-1 = ζ(1 + ζ + ζ2 + ... + ζn-1)
(2) Now ζ ≠ 0 [since 0n ≠ 1] and ζ ≠ 1
(3) Let x = 1 + ζ + ζ2 + ... + ζn-1
(4) Assume that x ≠ 0
(5) So, x = ζx [from step #1]
(6) Since we assume x ≠ 0, we can divide both sides by x to get 1 = ζ
(7) But this contradicts step #2 so we reject our assumption in step #3 and conclude that:
1 + ζ + ζ2 + ... + ζn-1 =0
QED
Corollary 1.1:
if ζ is a primitive n-th root of unity, then:
a = (-a) ζ + (-a)ζ2 + ... + (-a)ζn-1
Proof:
(1) From Lemma 1 above:
-1 = ζ + ζ2 + ... + ζn-1
(2) So, a = (-a)(ζ + ζ2 + ... + ζn-1 ) = (-a) ζ + (-a)ζ2 + ... + (-a)ζn-1
QED
Lemma 2:
if i ≡ j (mod q)
and
ζ is a primitive qth root of unity
Then:
ζi = ζj
Proof:
(1) i ≡ j (mod q) implies there exists integers r,s such that:
i +r*q = j + s*q
(2) So, it follows that:
ζi*(ζq)r = ζj*(ζq)s
(3) Since ζq = 1, we have:
ζi*1r = ζj*1s
which means that:
ζi = ζj
QED
Subscribe to:
Posts
(
Atom
)